Heterogeneous processing of bromine compounds by atmospheric aerosols: Relation to the ozone budget - Robinson, J.M.; Henson, B.F.; Dubey, M.K.; Casson, J.L.; Johal, M.S.; Wilson, K.R. (Los Alamos National Laboratory, 1998)
This is the final report of a three-year, Laboratory Directed Research and Development (LDRD) project at Los Alamos National Laboratory (LANL). The depletion of ozone, particularly above Antarctica, has been investigated extensively to formulate public policy on the use of halocarbons. While it has been shown that heterogeneous reactions of chlorine compounds on stratospheric particulates cause the ozone hole, little is known of the analogous bromine mechanisms, even though it has been recognized for two decades that catalytic destruction of ozone by bromine could be more efficient than chlorine. Furthermore, field measurements and modeling calculations suggest that these heterogeneous (gas/surface) reactions are not restricted to the Antarctic regions but occur globally. The authors have performed laboratory measurements of the uptake of bromine compounds and other halogens on simulated stratospheric aerosols to help elucidate their role in catalytic ozone destruction cycles. Their studies contribute to the data base required to make assessments of the effects of human activities on global change, including the Montreal Protocol.